2015
DOI: 10.13075/mp.5893.00104
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among 17–18 year old adolescents – Prevalence and association with sociodemographic, familial, sport, and scholastic factors

Abstract: Background: Though adolescence is recognised as a critical period for smoking prevention, there is a lack of research focused on this issue in Kosovo. The aim of this study has been to examine the gender-specific factors of influence (predictors) for smoking among adolescents in Pristina, Kosovo. Material and Methods: The study sample comprised 1002 adolescents at the age of 17-18 (366 boys, 636 girls), all of whom were in the school's 12th grade. The predictors included sociodemographic variables, familial (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 20 publications
(36 reference statements)
5
27
0
Order By: Relevance
“…All subjects were in their last year of high school education (i.e., 4th-year high school seniors). The sample was limited to this age group to be objectively comparable with studies conducted to date in the former Yugoslav territories [1,12,22]. Initially, 10 high schools for each Canton were selected by lottery, which resulted in 122 high-school senior classes and theoretical sample of 3676 children.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects were in their last year of high school education (i.e., 4th-year high school seniors). The sample was limited to this age group to be objectively comparable with studies conducted to date in the former Yugoslav territories [1,12,22]. Initially, 10 high schools for each Canton were selected by lottery, which resulted in 122 high-school senior classes and theoretical sample of 3676 children.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations done so far frequently reported gender-specific relationships among different factors of influence on SUM [2,12,22]. For example, parental-variables (i.e., conflict with parents, lower parental monitoring) are indicated as risk factors for alcohol drinking in girls, but not in boys [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] However, when sport participation was analysed more specifically, there were some conflicting findings with the association between sports and cigarette smoking. [26][27][28] For example, in a recent study, authors found that adolescents who had stopped participating in a sport were at high risk of misusing substances, while lower competitive achievement in sports was found to be associated with a higher likelihood of cigarette smoking. 3 5 27 Again, owing to the cross-sectional study design, the causality is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…A study of over 970 adolescents in Bosnia and Herzegovina, 17 to 18 years old, showed that 30% of young men and 32% of young women smoke (38), and some of them started smoking as early as 13 years of age (39). The incidence of smoking is also reported to be high in Croatia (27.4%) (40) and Kosovo (31% for adolescent males and 40% for adolescent women) (41). Although a significant decrease in tobacco consumption has been observed globally from 2002 to 2010, this trend is still lagging behind in Eastern Europe (42).…”
Section: Discussionmentioning
confidence: 99%